Factors Associated with Adherence to Micronutrient Powder (Baal Vita) among Children Aged 6-23 Months in Rasuwa District. - Timalsina,Ashish (2020)
ABSTRACT: Introduction Breastfeeding is not enough to fulfill the nutrition requirement after six months of age, so it is the right time to introduce complementary feeding to the child. This period is vulnerable to become undernutrition. The most common cause of anemia among children aged 6-23 months is iron deficiency. The most appropriate strategy to address the iron deficiency could be dietary supplementation and fortification. The adherence to iron syrup or tablets is not satisfactory than that of powder form. Thus, MNP containing 15 different types of micronutrients was introduced which can be mixed with semi-solid food to feed the children age 6-23 months. In Nepal about 69% of children aged 6-23 months were anemic and the Government of Nepal had introduced supplementation of Micro Nutrient Powder (MNP) as the local name "Baal Vita" since 2009. The MNP supplementation program has been implemented in 41 districts of Nepal. Home fortification of MNP is a major strategy of the government of Nepal to address the anemia. So, the main objective of this study is to determine the adherence to MNP among children aged 6-23 months in Rasuwa district of Nepal. Methodology A cross-sectional study was carried out in the Uttargaya rural municipality and the Kalika rural municipality of Rasuwa district among 200 mothers of children aged 6-23 months of age. Simple random sampling was used to select the rural municipalities and proportionate to population size was used to select the children for interviews. Data were entered in Epi Data version 3.1 and analysis was done in STATA version 13. Univariate logistic regression analysis was performed to determine the statistically significant differences between a dependent and independent variables. Multivariate logistic regression was done to obtain adjusted odds ration with 95% C.I. Findings Out of 200 mothers interviewed, 115 mothers who received 60 sachets of MNP were used for analysis. The mean age of the mother was 25. 29±5. 32 years and the mean age of children was 14. 66±5. 23 months. About half of the mothers had adequate knowledge of MNP and anemia. Most of the mothers accepted the properties of MNP. Almost all mothers told the right procedure for feeding a child with MNP. The mother having one child of under 5 years, MNP received from HF and mothers who accepted the properties of MNP were statistically significant. The mother who received MNP from HF was almost two times more likely to adhere to the MNP. The mothers who accepted the MNP were almost two times more likely to adhere to the MNP than the mother who did not accept the MNP. Conclusion The adherence to MNP was significantly associated with the acceptability of MNP received from a health facility. Knowledge of mother's on anemia and MNP did not differ significantly to the adherence of MNP indicates that mothers were following the instructions on MNP without knowing its reason to use. Effective nutrition education, counseling and follow up to the mothers are essential to improve adherence to MNP. A cross sectional qualitative studies should be carried out to explore the predictors of adherence to MNP at the community level as well as a cross-sectional study should be conducted to determine the level of Hemoglobin at different level of adherence.